0041 Work-related ill-health in doctors working in great britain: incidence rates and trends. (21st August 2017) - Zhou, Anli Yue; Carder, Melanie; Gittins, Matthew; Agius, Raymond
Abstract : Background: Higher mental ill-health (MIH) prevalence rates have been reported in doctors compared to other professionals. Previous studies have investigated MIH prevalence in doctors, but trends in their incidence rates (IR) of work-related mental ill-health (WRMIH) have not yet been reported. Objectives: This study measured IR and IR trends of work-related ill-health (WRIH) and WRMIH in doctors in comparison to nurses, paramedics, social workers and teachers as reported by occupational physicians to the Occupational Physician Reporting Activity (OPRA) Network. Methods: OPRA reported WRIH and WRMIH incidence data was collected prospectively from 2001–2014. OPRA reporting denominators were surveyed during two triennial periods (2005–07; 2008–10) and corrections undertaken to improve IR accuracy. IR trends were investigated using 'multilevel' regression. Results: Between 2005–2010, 1097 WRIH cases were reported in doctors, of which 905 (82.5%) were WRMIH. Annual average WRIH and WRMIH IR in doctors were 515 and 431 per 1 00 000 employed, respectively, with little variation between the two triennia. Compared to doctors, higher IR for WRIH and WRMIH were observed in nurses and paramedics. From 2001–2014, doctors demonstrated an annual average IR increase for WRIH (6.1% [95%CI 2.2%, 10.1%]), whereas teachers and nurses demonstrated decreasing trends (−4.3% [95%CI −5.3%, −1.0%] and −3.2% [95%CI −5.3%, −1.0%]). Doctors also demonstrated an annual average IR increase for WRMIH (6.5% [95%CI 2.2%, 11%]), whereas teachers showed a decreasing trend (−3.9% [95%CI −6.5%, −1.2%]). Conclusions: Nurses and paramedics demonstrated higher IR than doctors but trends analyses suggested that IR is increasing for both WRIH and WRMIH only in doctors.